Dielectric characterization of paraelectric particle-loaded polymer matrix composites and commercial photoresins at W-band frequencies. Issue 2 (February 2023) - Forstmeier, Michael; Yuan, Mengxue; Perini, Steve; Lanagan, Michael; Foley, Brian
Abstract: This work presents W-band (75–110 GHz) dielectric characterization of commercially available photoresins in their neat state, as well as in polymer matrix composite (PMC) mixtures with various loading concentrations of the paraelectric barium strontium titanate (BST). Due to difficulties 3D printing the BST-loaded PMC resins detailed within, a custom curing and casting process was used to fabricate testable PMC samples, which were synthesized to demonstrate the dielectric functionalization of the underlying polymer matrix. Dielectric characterization of the PMCs confirmed the functionalization of our composites when compared to the commercial photoresins. For example, a volumetric loading concentration of 25 vol % BST increased the dielectric permittivity ( εr ) from 2.78 to 9.60 and the loss tangent (tanδ) from 0.022 to 0.114. These results indicate that the realization of UV-cured photoresins with "designer-dielectric" functionalization based on vol % of filler are strong candidates for use in stereolithography (SLA) 3D printing applications. To accomplish this, and with a special interest for radio/microwave/terahertz (RF/MW/THz) applications, we highlight the need for both (a) better photoresin matrix materials with lower intrinsic tanδ and (b) selection criteria related to the size/geometry and electronic properties of potential filler materials to maintain the printability of PMC photoresins in SLA systems.